Passivation Mechanism in Highly Luminescent Nanocomposite‐Based CH3NH3PbBr3 Perovskite Nanocrystals - Jaume Noguera‐Gómez; Víctor Sagra‐Rodríguez; Vladimir S. Chirvony; Miriam Minguez‐Avellan; Mahesh Eledath‐Changarath; Juan F. Sánchez‐Royo; Juan P. Martínez‐Pastor; Pablo P. Boix; Rafael Abargues (Small Science)
Water exposure significantly impacts the structure and photoluminescence (PL) of metal halide perovskites. However, humid conditions can enable the in situ synthesis of methylammonium lead bromide (MAPbBr3) perovskite nanocrystals (NCs) within a nickel acetate matrix, achieving PL quantum yields (PLQY) of up to 80%. The water‐driven formation and transformation of MAPbBr3 is presented, highlighting the crucial role of acetate. Comprehensive optical and structural analyses reveal that low relative humidity (RH < 20%) favors the formation of non‐emissive MA4PbBr6 (0D) and hydroxide species (PbBrOH, OH−) . Exposure to higher RH induces a structural reorganization from 0D MA4PbBr6 to 3D MAPbBr3 via a MABr‐stripping mechanism, forming NCs with enhanced PLQY. Removing ambient humidity quenches PL, a process that is reversible due to hydroxide‐mediated reactions controlled by dual acid‐base nature of the acetic acid/acetate system. Unlike previous reports, the findings reveal that hydroxide ions reversibly bind to NCs, passivating traps and improving stability. Acetate's basicity plays a critical role in generating OH−, promoting the passivation, stability, and enhanced optical properties of the perovskite nanocomposites.